Isolation and characterization of a fibrinogen-clotting enzyme from venom of the snake, Lachesis muta muta(Peruvian bushmaster) - Yarleque A. (1989)
A. Yarleque, S. Campos, E. Escobar, F. Lazo, N. Sanchez, S. Hyslop, N. A. Marsh, P. J. Butterworth and R. G. Price. Isolation and characterization of a fibrinogen-clotting enzyme from venom of the snake Lachesis muta muta(Peruvian bushmaster). Toxicon27, 1189–1197, 1989.—A fibrinogen-clotting enzyme from the venom of the Peruvian bushmaster snake was purified to homogeneity by gel filtration on Sephadex G-100 followed by DEAE-cellulose ion-exchange chromatography using a linear ionic strength gradient with NaCl.